New distribution data of the vulnerable Mertensiella caucasica from Gümüşhane, Turkey - Muammer Kurnaz (Nature Conservation Research: Zapovednaâ Nauka, 2019)
The Caucasian salamander, Mertensiella caucasica, is a vulnerable species, distributed in a restricted area from the southwest of Georgia to the northeast of Turkey. This study presents five new localities from the Gümüşhane province in Turkey. The new localities extent the known distribution by about 40 km southwards. We determine the species' potential distribution in this province. The habitat of M. caucasica has been predicted to shrink in the future and localities on the range boundary such as presented here will be important to understand the species' tolerance.